2017
DOI: 10.2136/sssaj2016.09.0277
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Fluxes and Soil Oxygen Dynamics of Soil Treated with Cow Urine

Abstract: Abbreviations: CWC, cold water carbon; DOE, day of experiment; DI, deionized water; HWC, hot water carbon; GLM, general linear model; N 2 OR, nitrous oxide reductase; SWLR, structure-dependent water-induced linerar reduction model; WFPS, water-filled pore space. N itrous oxide is a potent greenhouse gas (GHG) that contributes to climate change, and it is projected to be the dominant ozone-depleting substance emitted in the 21st century (Ravishankara et al., 2009). Increases in atmospheric N 2 O concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 54 publications
4
22
1
Order By: Relevance
“…These reductions were consistent with those from chamber measurements at the Edmonton South Campus Farm (Lin et al, 2018) and with those from a limited number of studies elsewhere, in which persistent effects of NI in reducing overwinter N 2 O emissions have been found (e.g. Pfab et al, 2012), indicating the importance of f T s in Eq. (1).…”
Section: Ni Effects On Barley Silage Yieldssupporting
confidence: 89%
See 1 more Smart Citation
“…These reductions were consistent with those from chamber measurements at the Edmonton South Campus Farm (Lin et al, 2018) and with those from a limited number of studies elsewhere, in which persistent effects of NI in reducing overwinter N 2 O emissions have been found (e.g. Pfab et al, 2012), indicating the importance of f T s in Eq. (1).…”
Section: Ni Effects On Barley Silage Yieldssupporting
confidence: 89%
“…These O 2 transfers were sustained by concentration gradients from O 2g to O 2s and from O 2s to O 2 at microbial surfaces (O 2m ) so that declines in O 2s (Fig. 3) (Nguyen et al, 2017;Owens et al, 2017). These O 2 deficits were modelled using a K m for O 2m of 10 µM by nitrifiers (Sect.…”
Section: Ni Effects On Barley Silage Yieldsmentioning
confidence: 99%
“…An in situ study by Friedl et al (2017) examined the potential for nitrification inhibitors to reduce N 2 losses from intensively managed subtropical pastures, found that N 2 losses were triggered when D p / D o values indicated the development of anaerobic conditions (< 0.02, Stepniewski, 1980). Owens et al (2017) examined N 2 O fluxes from ruminant urine–affected soil, with respect to WFPS and D p / D o , and reported that D p / D o explained the variability in N 2 O fluxes better than WFPS, 73 and 65% respectively, and that, consistent with earlier laboratory studies (Balaine et al, 2013; Balaine et al, 2016), N 2 O emissions become elevated as D p / D o declined toward a value of 0.006. In support of the theory advocated by Farquharson and Baldock (2008) the literature shows that there exists a relatively wide range of WFPS producing enhanced N 2 O fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, N 2 O flux rates were found to peak under relatively water‐saturated conditions and sharply decrease with decreasing soil moisture (Schaufler et al, 2010). In intensively grazed pastures wet soil conditions, resulting from rainfall or irrigation soon after grazing, have been shown to result in high N 2 O emissions due to enhanced denitrification (Luo et al, 2013; Owens et al, 2017). Water‐filled pore space (WFPS), the ratio of volumetric moisture content to total porosity, has commonly been used to express the degree of moisture availability in the pore space to explain N 2 O emissions from soil (Ball, 2013).…”
mentioning
confidence: 99%
“…Our results suggest that it will be difficult to conduct a meaningful meta‐analysis of the published findings, if all studies use unique sampling protocols and do not provide detailed information on temporal changes in soil moisture and temperature (Balaine et al, 2013). For example, in South Dakota, Lehman and Osborne (2016) collected gas samples at approximately 1000 h, whereas in Indiana, Owens et al (2017) collected samples between 1000 and 1200 h. In Colorado, Halvorson and Del Grosso (2012) collected samples in midmorning, and in Minnesota, Venterea and Coulter (2015) collected samples between 1000 and 1300 h.…”
Section: Discussionmentioning
confidence: 99%